Research on Dynamic Optimization Balance of Crank-group Driving Mechanism in Plane based on Matlab - Weiliang Yan (Jixie chuandong)
By analyzing the inertia force and inertia moment in the plane of crank-group driving mechanism，the dynamic optimization balance model of the mechanism is established. Taking the crank-group mechanism of three crank pairs as an example，the specific optimization model is solved by using Matlab optimization toolbox. The results show that the dynamic optimization balance method of crank-group driving mechanism can greatly reduce the inertial force and moment of inertia of the mechanism，and the optimization balance only needs to add the balance mass of the determined mass at the determined position in the opposite direction of the crank length according to the optimization results just a couple of pieces. This method has high operability and practical application value，and has certain guiding significance for the rapid balancing and popularization of the mechanism.